Additional treatment of biologically treated wastewater using environmentally friendly sorbents - Ali, Haider; Mažeikienė, Aušra; Paliulis, Dainius (International Conference “Environmental Engineering”, 2026)
Biological wastewater treatment is effective for the removal of organic matter; however, residual nitrogen and phosphorus often remain in the treated effluent, contributing to eutrophication of receiving water bodies. Small and decentralized wastewater treatment plants are particularly vulnerable to fluctuating influent loads and operational constraints, which can result in elevated concentrations of ammonium and phosphate in the final effluent. This study evaluates environmentally friendly zeolite-containing sorbents as tertiary filtration media for polishing biologically treated domestic wastewater. Column filtration experiments were conducted using wastewater after biological treatment, and the performance of four sorbents was assessed by monitoring phosphate phosphorus (PO₄-P), ammonium nitrogen (NH₄-N), nitrate nitrogen (NO₃-N), and pH. The results demonstrate that zeolite-based sorbents can effectively reduce nutrient concentrations, with notable differences in removal efficiency among the tested materials. The findings indicate that sorbent-based tertiary treatment represents a sustainable and low-energy option for reducing nutrient loads from small-scale wastewater treatment facilities, contributing to improved water quality and resource-oriented wastewater management.
Keywords: wastewater; nutrient removal; adsorption; phosphate; ammonium; tertiary treatment